The next steps for apprenticeship : European synthesis report - (:unkn) unknown (Publications Office of the European Union, 2021)
"In a context of considerable interest in apprenticeship in recent years, Cedefop and the OECD decided to explore its future from the perspective of a number of megatrends, including sociodemographic changes, the accelerated adoption of emerging technologies and new forms of work organisation. They also considered how these trends have affected, and will continue to affect, the design and delivery of apprenticeship in European and OECD countries. The combination of the emerging economic crisis as an aftermath of the Covid-19 pandemic, together with long-term structural trends affecting global economies, will entail a profound transformation of the world of work and require effective policy responses in the years to come. This publication provides insights from 16 papers by researchers from Europe, Australia and the United States; nine were presented and discussed among policy-makers, practitioners and researchers during the joint CedefopOECD symposium on the future of apprenticeship held in October 2019 in Paris. Evidence and analysis in these papers will help inform political decisions shaping the future of apprenticeship." (editor; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; I 2.2 Europa; Berufsausbildung; Zukunftsperspektive; Demografischer Wandel; Arbeitsorganisation; Technischer Wandel; Einflussfaktor; OECD-Staaten; Europa